Estratégias dos agricultores entre arroz e soja, produção percepções. O exemplo de Cachoeira do Sul/RS, Brasil - Frédéric Fortunel; Márcia dos Santos Ramos Berreta; Benjamin Dias Osorio Filho (Confins)
Since the beginning of the 20th century, rice has increased in surface area and economic weight in southern Brazil, where the land and the economy are suitable. The municipio of Cachoeira do Sul, located at the central depression of the state of Rio Grande do Sul, is the symbol of the cereal that is part of the traditional diet. It is the national capital of rice, which nevertheless has troubles keeping its place in the rural boundaries, as over the last 50 years there has been a relative decline in rice production compared with soybean production. To understand the issues at stake in this relationship between the cereal and the leguminous plant, we call upon two distinct interpretative grids. The first part deals with spatial concerns, taking into account the effects of location, access to water and land tenure patterns to explain cropping distributions and technical choices. The second part deals with identity issues, questioning the region's historic rice-growing vocation in the face of major changes.